Modeling genetic mosaicism of the mammalian target of rapamycin pathway in the cerebral cortex - Feliciano, David M. (Frontiers in Mammal Science, 2023)
The capacity to integrate complex sensory cues and to coordinate an adequate behavioral response often requires integration of information within the outermost part of the mammalian brain called the cerebral cortex. The laminar and columnar cytoarchitecture of the cerebral cortex contains neurons that establish proximal and distal connections. Genetically encoded transcription factors ensure the generation of the appropriate number, types, locations, and connections of cortical neurons. However, somatic mutations that alter cortical development provide evidence that post-transcriptional regulation is equally important. An example is that somatic mutations in regulators and substrates of mammalian target of rapamycin (mTOR) are associated with neuropsychiatric and neurological manifestations. mTOR is a protein kinase that phosphorylates substrates that control mRNA translation and anabolic processes. Numerous challenges remain in uncovering the mechanisms by which mutations in regulators and substrates of mTOR impact behavior. Here, evidence is provided that somatic mosaicism can be modeled in the developing murine cerebral cortex which may have clinical significance.